Basic histology : text & atlas - Junqueira, Luiz Carlos Ucho? a; Carneiro, Jose? . (New York : McGraw-Hill, Medical Pub. Division, 2005)
Recognized as the leading medical histology text in the world, Basic Histology: Text & Atlas offers the most comprehensive approach to the relationship between tissue structure and function and the physiologic response in the human body. Completely updated and redesigned in true-to-life color, it continues to pave the way as the most authoritative text of its kind. Showcases more than 600 high-quality photomicrographs, electron micrographs, and illustrations, 500 of which are in full color; emphasizes cell biology as the most fundamental approach to understanding structure and function of tissues and organs; clear and comprehensive explanations of microscopic anatomy; full-color photomicrographs prepared from new tissue samples feature distinctive labeling that clearly pinpoints the elements of interest and enhances the didactic nature of the book; bonus image library CD-ROM includes all of the photomicrographs and illustrations in the book; medical applications relate histology to pathobiology, diagnosis, and clinical aspects of disease; key concepts highlighted in each chapter; newly revised and updated to reflect recent findings and interpretations in the field, including molecular biology, intercellular communications, human genomics, and the structure and function of specific organ systems; impressive collection of photomicrographs and illustrations summarizes morphologic and functional features of cells, tissues, and organs; and concise discussion of the structure and function of cells, the four basic body tissues, and each organ and organ system. - Back cover.
Original title : Histologia basica, 8th ed. by Editora Gunanabara Koogan S.A., Rio de Janeiro, Brazil.
Includes bibliographical references and index.
Keywords: Histology